Ten years of intensive late-winter surveys for waterfowl corpses on the north-west shore of the Wash, England - Pilcher, R E M; Beer, J V; Cook, W A (Wildfowl, 1974)
A stretch of coast was searched for corpses late in the winter of 10 years. The results enable an assessment of the significance of waterfowl mortality in the extremely hard winter of 1962-1963. Only Shelduck Tadorna tadorna and Redshank Tringa totanus suffered mortality high enough markedly to depress their populations over several years. Comparisons are made with the results of other similar corpse surveys. The extent of oil pollution was measured and some information on the incidence of pathological conditions obtained.